Complicated Community-Acquired Staphylococcus Endocarditis and Multiple Lung Abscesses: Case Report and Review of Literature - Musa A. Garbati; Imad M. Tleyjeh; Abdullah A. Abba (Case Reports in Infectious Diseases)
Background. Isolated tricuspid valve endocarditis in the absence of risk factors in the community setting is very rare and can be easily missed in patients with hitherto normal valves. Case Presentation. We present a case of a 49 year old gentleman who presented with generalized body aches, fever, and jaundice and was initial diagnosed as hepatitis. He subsequently developed recurrent episodes of panic attacks and shortness of breath and later multiple skin abscesses. Further investigations excluded pulmonary embolism but revealed multiple abscesses in the body including the lungs. Blood cultures and culture from abscesses grew S. aureus. An initial transthoracic echocardiogram was normal. A transesophageal echocardiogram subsequently confirmed endocarditis on a normal natural tricuspid valve and multiple lung abscesses. He was successfully treated with appropriate antibiotics. Conclusion. We discuss the pathogenesis of this patient's presentation highlight the need for assessment and proper evaluation of patients with unexplained bacteremia.